Engaging peers to promote well‐being and inclusion of newcomer students: A call for equity‐informed peer interventions. Issue 12 (25th November 2021) - Crooks, Claire V.; Kubishyn, Nataliya; Noyes, Amira; Kayssi, Gina
Abstract: Although newcomer youth demonstrate high levels of resiliency, many experience challenges in emotional, linguistic, academic, and social functioning. Over the past decade, some promising school‐based psychosocial interventions for newcomer youth have been developed. These interventions are necessary, but not sufficient to promote well‐being. Without attention to the larger context, focusing solely on the skills and adjustment of newcomer youth could potentially stigmatize students further. There is a need to engage non‐newcomer peers for two reasons. First, peer relationships and inclusion are important predictors of well‐being. Second, from an equity lens, there is a need to create environments that promote youth well‐being; at the very least, these environments must engage non‐newcomer youth in recognizing and combatting discrimination. This study outlines the need for peer‐focused programming to support newcomers and describes existing research on interventions developed to promote peer relationships (e.g., mentoring) or reduce discrimination (e.g., teacher‐led discrimination reduction approaches). We identify other intervention models that could inform how to add an equity lens to school mental health intervention, including how a gender‐sexuality alliance model could be adapted, and how equity considerations could be integrated into bystander approaches. We conclude with specific implications and recommendations for embedding equity into school mental health.